Argan oil prevents down-regulation induced by endotoxin on liver fatty acid oxidation and gluconeogenesis and on peroxisome proliferator-activated receptor gamma coactivator-1α, (PGC-1α), peroxisome proliferator-activated receptor α (PPARα) and estrogen related receptor α (ERRα) - El Kebbaj, Riad (Biochim Open, 2015)
In patients with sepsis, liver metabolism and its capacity to provide other organs with energetic substrates are impaired. This and many other pathophysiological changes seen in human patients are reproduced in mice injected with purified endotoxin (lipopolysaccharide, LPS). In the present study, down-regulation of genes involved in hepatic fatty acid oxidation (FAOx) and gluconeogenesis in mice exposed to LPS was challenged by nutritional intervention with Argan oil. Mice given a standard chow supplemented or not with either 6% (w/w) Argan oil (AO) or 6% (w/w) olive oil (OO) prior to exposure to LPS were explored for liver gene expressions assessed by mRNA transcript levels and/or enzyme activities. AO (or OO) food supplementation reveals that, in LPS-treated mice, hepatic expression of genes involved in FAOx and gluconeogenesis was preserved. This preventive protection might be related to the recovery of the gene expressions of nuclear receptors peroxisome proliferator-activated receptor α (PPARα) and estrogen related receptor α (ERRα) and their coactivator peroxisome proliferator-activated receptor gamma coactivator-1α, (PGC-1α). These preventive mechanisms conveyed by AO against LPS-induced metabolic dysregulation might add new therapeutic potentialities in the management of human sepsis.